Does pregnancy affect medical ethical decision making? - Hammerman, C (1998)
OBJECTIVE: We studied and compared the attitudes of pregnant women v new mothers in an attempt to confirm changing patterns of maternal response towards medical ethical decision making in critically ill or malformed neonates. DESIGN: Data were obtained by questionnaires divided into three sections: 1. sociodemographic; 2. Theoretical principles which might be utilised in the decision-making process; 3. Hypothetical case scenarios, each followed by possible treatment options. RESULTS: Pregnant women (n = 545) consistently requested less aggressive medical intervention for the hypothetical cases than did new mothers (n = 250) [Trisomy 18: 57% v 42%; p = 0.0004; Asphyxia: 75% v 63%; p = 0.0017; Down's syndrome 81% v 62%; p = 0.0001; LBW 85% v 75%; p = 0.004]. Significant differences were also observed in the responses to the theoretical principles, with pregnant women attributing less importance to preserving life at all cost, while being more concerned with physical and emotional pain and suffering, with financial cost, and with the infant's potential for future productivity.